Parallel Mesh Refinement of Higher Order Finite Elements for Electronic Structure Calculations (Communications in Computational Physics, 2008)
The finite element method is a promising method for electronic structurecalculations. In this paper, a new parallel mesh refinement method for electronic structure calculations is presented. Some properties of the method are investigated to makeit more efficient and more convenient for implementation. Several practical issues suchas distributed memory parallel computation, less tetrahedra prototypes, and the assignment of the mesh elements carried out independently in each sub-domain will bediscussed. The numerical experiments on the periodic system, cluster and nano-tubeare presented to demonstrate the effectiveness of the proposed method.